The impact of mental health disorders and job demands on the individual job performance of construction workers - Kazar, Gokhan; Rahmanzadeh, Pourya (OXFORD UNIV PRESS, 2024)
Objectives: Understanding the impact of job demands and mental health disorders on individual job performance is crucial to achieving a more productive workforce and should be empirically investigated. Therefore, the main purpose of this study was to assess the impact of job demands and mental health disorders on individual job performance among construction workers. In addition, we examined the interaction effect between job demands and some demographic characteristics (income, marital status, experience, and area of residence) on the job performance of construction workers in 2 dimensions. Methods: For this purpose, a new conceptual model and 3 different hypotheses were introduced. A survey was designed and administered to 513 construction workers. Whereas the measurement items regarding demographic characteristics, job demands, and mental health disorders were addressed to construction workers, the last part related to job performance of construction workers was conducted with site managers of the workers to obtain more objective results. A structural equation modeling approach was adopted to assess the validity of the model and to test the hypotheses. Results: The results of this study show that whereas job demands have a significant and high impact on individual job performance, the effect of mental health disorders on job performance is significant at a moderate level. In addition, the demographic characteristics of marital status and area of residence have a significant interaction effect on job performance when combined with job demands. Conclusion: Providing individualized support systems, resources, and opportunities for construction workers can help mitigate the negative effects of excessive demands and mental disorders on labor productivity.
Keywords: mental health disorders; worker productivity; job demands; structural equation modeling; interaction effect; demographic characteristics; LABOR PRODUCTIVITY; DISTRESS; PROJECTS; STRESS; Public, Environmental & Occupational Health